2023
DOI: 10.3390/f14112213
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness of Wood Substrates after Grinding and Its Influence on the Modification Effect of Structural Color Layers

Yi Liu,
Jing Hu,
Wei Xu

Abstract: For a comprehensive understanding of the surface roughness of wood substrates after grinding and its influence on the construction of surface structural color layers (SCLs) and the effect of color production, four typical diffuse-porous wood species were investigated by grinding with abrasive belts of different grits. The results indicated that an abrasive belt of suitable grit was required to form the flattest surface for different wood species. Notably, 400-grit abrasive belts can be used for quaking aspen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It can be seen from Figure 8B that, compared with other diffuse porous woods such as aspen and hard maple [31], the wide rays of beech wood were its typical anatomical structure. From the three-section micrographs of beech, it could be seen that the rays, es- When the fourth and fifth brushings were performed, the reflection curve continued overall toward a higher reflectance for the structural color layer of the tangential section of the wood, with the peak reflectance at 501 nm of 92.4% and 96.5% (T-4 and T-5 in Figure 7), respectively, which had gentler slopes of the peak shape relative to the structural color layer constructed in the second and third brushings.…”
Section: Influence Of Anatomical Characteristics Of European Beech Wo...mentioning
confidence: 96%
See 3 more Smart Citations
“…It can be seen from Figure 8B that, compared with other diffuse porous woods such as aspen and hard maple [31], the wide rays of beech wood were its typical anatomical structure. From the three-section micrographs of beech, it could be seen that the rays, es- When the fourth and fifth brushings were performed, the reflection curve continued overall toward a higher reflectance for the structural color layer of the tangential section of the wood, with the peak reflectance at 501 nm of 92.4% and 96.5% (T-4 and T-5 in Figure 7), respectively, which had gentler slopes of the peak shape relative to the structural color layer constructed in the second and third brushings.…”
Section: Influence Of Anatomical Characteristics Of European Beech Wo...mentioning
confidence: 96%
“…In addition to the ray tissue, it was widely distributed with vessels which had a much larger inner diameter than the ray cells. In previous studies, it was found that the roughness of the wood surface would affect the formation of ordered structures by microspheres [31]. Therefore, the ray region provided excellent substrate flatness for the structural color layer construction, while the microstructure of other areas mainly composed of vessels and wood fibers was more uneven, which was not conducive to the self-assembly of microspheres into well-ordered structures.…”
Section: Influence Of Anatomical Characteristics Of European Beech Wo...mentioning
confidence: 98%
See 2 more Smart Citations
“…Secondly, the seven timbers include six broadleaf and one coniferous timber, representing two typical types of timber. Crucially, the choice of these six broadleaf timbers builds upon previous research [20] and exhibits variations in type, number, cell diameter, and smoothness of vessels, offering a degree of representativeness. Additionally, the selection encompasses woods with diverse anatomical structures and cell diameters, fulfilling our research objective of investigating the impact of wood surface cell characteristics on the formation of structural color layers.…”
Section: Materials and Woodsmentioning
confidence: 99%